2021
DOI: 10.1021/acs.energyfuels.1c00113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propane Addition and Oxygen Enrichment on the Flame Characteristics of Biogas

Abstract: Mixing biogas with other fuels or increasing the oxygen fraction in the oxidizer can improve the combustion performance of biogas. In this study, we investigated the effects of propane addition and oxygen enrichment on the flame characteristics of biogas with a constant heating value in a half-open duct. The evolution of the flame structure revealed that the tulip structure took on two types of patterns at the oxygen fraction θ = 0.21. However, there was no salient tulip flame formation when θ > 0.21. Oxygen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…18 The ECR curves were fitted by MATLAB with an ECRTOOLS code. 19 X-ray photoelectron spectroscopy (XPS) was obtained on a Thermo Scientific K-Alpha+ spectrophotometer with monochromatized Al K α X-ray (hν = 1486.6 eV) radiation in ultrahigh vacuum (<5 x 10 −9 mBar). All experimental data were corrected using C 1s of 284.8 eV.…”
Section: Methodsmentioning
confidence: 99%
“…18 The ECR curves were fitted by MATLAB with an ECRTOOLS code. 19 X-ray photoelectron spectroscopy (XPS) was obtained on a Thermo Scientific K-Alpha+ spectrophotometer with monochromatized Al K α X-ray (hν = 1486.6 eV) radiation in ultrahigh vacuum (<5 x 10 −9 mBar). All experimental data were corrected using C 1s of 284.8 eV.…”
Section: Methodsmentioning
confidence: 99%
“…Wang and colleagues investigated how adding propane and oxygen to biogas affects combustion instability [75]. The results showed that oxygen enrichment increased the explosion pressure of the flame.…”
Section: Properties Of Gas Mixturesmentioning
confidence: 99%